PENGARUH KONSENTRASI GLISEROL DAN TAPIOKA TERHADAP KARAKTERISTIK BIODEGRADABLE FILM BERBASIS AMPAS RUMPUT LAUT Eucheuma cottonii [The effects of glycerol and tapioca concentration on the characteristics of Eucheuma cottonii seaweed dreg-based biodegradabl - Zulferiyenni Zulferiyenni; Marniza Marniza; Erli Novida Sari (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
This research was aimed to find the appropriate combination of glycerol and tapioca concentration in the production of Eucheuma cottonii seaweed dreg-based biodegradable films. A two factors experiment was arranged in a Complete Randomized Design with three replications. The first factor was three levels of glycerol concentration : 0.25%; 0.5% and 0.75%. The second factor was three levels of tapioca concentration: 5%; 6% and 7%. The data of visual observation, Fourier transform infra red analysis, biodegradability and water vapor permeability were analyzed descriptively. The tensile strength, elongation and solubility of biodegradable films were analyzed using by ANOVA. The homogenity was use barlett test and the aditivity was use Tukey test. The data were continue by HSD test at 5% level of significant. The concentration of glycerol and tapioca significant effects on tensile strength and percent elongation, but not on solubility. The best characteristics of the Eucheuma cottonii seaweed dreg-based biodegradable film was produced from a combination of 0.25% of glycerol and 7% of tapioca concentration. The best biodegradabe film had characteristic of an f 53.92 MPa tensile strength, an 3.647 % elongation, 86.17% solubility, 14 day biodegradability, 6.13 g/(m2/day) water vapor permeability . The addition of glycerol and tapioca concentration in producting of Eucheuma cottonii seaweed dreg-based biodegradable film has caused the film characteristics more plastic and homogeneous. Keywords: Biodegradable film, Fourier transform infra red, percent elongation, seaweed dreg, tensile strength, water vapor permeability